Pre-Service Biology Teachers’ Mathematics Anxiety - Tamba, Kimura Patar; Bermuli, Jessica Elfani (Department of Mathematics Education Program IPI Garut, 2023)
Kemampuan kuantitatif dibutuhkan calon guru biologi dalam memahami fenomena biologis. Hal pertama yang perlu dilakukan dalam menyelesaikan masalah ini adalah perlunya eksplorasi kondisi kecemasan matematika calon guru biologi. Penelitian ini bertujuan mengeksplorasi tingkat kecemasan matematika calon guru biologi dan perbedaannya berdasarkan gender dan angkatan masuk kuliah. Data dikumpulkan dengan menggunakan kuisioner AMAS (Abbreviated Math Anxiety Scale). Data dianalisis dengan menggunakan statistic deskriptif, uji anova satu arah, dan uji Kruskal-Wallis. Hasil penelitian menunjukkan calon guru biologi memiliki tingkat kecemasan matematika dan kecemasan belajar matematika berdasarkan angkatan dan gender berada pada kategori sedang. Sementara kecemasan evaluasi matematika berada pada kategori tinggi berdasarkan angkatan dan gender. Hasil penelitian juga menunjukkan tidak terdapat perbedaan kecemasan matematika, kecemasan belajar matematika, kecemasan atas evaluasi matematika berdasarkan gender dan angkatan. Hasil penelitian ini layak menjadi perhatian dalam pendidikan biologi bahwa perlu dikonstruksi suatu desain didaktis ataupun perubahan kurikulum yang mendorong integrasi dan interdisiplinari matematika dan biologi sehingga kecemasan matematika dapat berkurang. Quantitative ability is needed by prospective biology teachers in understanding biological phenomena. The first thing that needs to be done in solving this problem is the need to explore the condition of pre-service biology teachers’ mathematics anxiety. This study aims to explore the mathematics anxiety level of pre-service biology teachers and their differences by gender and cohort. Data were collected using the AMAS (Abbreviated Math Anxiety Scale) questionnaire. Data were analyzed using descriptive statistics, one-way ANOVA test, and Kruskal-Wallis test. The results showed that pre-service biology teachers had mathematics anxiety levels and mathematics learning anxiety based on cohort and gender were in the medium category. Meanwhile, mathematics evaluation anxiety is in the high category based on cohort and gender. The results also showed that there was no difference between mathematics anxiety, mathematics learning anxiety, anxiety over mathematics evaluation based on gender and cohort. The results of this study deserve attention in biology education that it is necessary to construct a didactic design or curriculum change that encourages integration and interdisciplinary mathematics and biology so that mathematics anxiety can be reduced.